2018
DOI: 10.1016/j.jval.2018.09.2277
|View full text |Cite
|
Sign up to set email alerts
|

Prm157 - The Impact of Landmark Response on Overall Survival: Implications for the Economic Evaluation of Immune-Therapy (I-O) Treatment in Small Cell Lung Cancer (Sclc)

Abstract: PFS (e.g. lognormal, Weibull) and a correlation parameter of the bivariate Normal distribution. Extrapolation functions can be different for PFS and OS. The uncertainty around the parameter estimates is assessed by using asymptotic properties of Maximum Likelihood estimates. We compute the total uncertainty around the parameter estimates by means of the Frobenius norm of the variance-covariance matrices. RESULTS: The total uncertainty associated with the independent modelling of OS and PFS is 0.0064, whereas t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…Partitioned survival models are a well-established approach in economic evaluations of immuno-oncology agents, and the base-case used in this paper was validated by a number of sensitivity analyses. An earlier landmark response analysis of nivolumab data from CheckMate 032 (November 2017 database lock) showed that response at the 4-month landmark time point was associated with significantly longer OS [27]. The findings at this time point were also consistent with sensitivity analyses with alternative 2-and 6-month landmarks.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Partitioned survival models are a well-established approach in economic evaluations of immuno-oncology agents, and the base-case used in this paper was validated by a number of sensitivity analyses. An earlier landmark response analysis of nivolumab data from CheckMate 032 (November 2017 database lock) showed that response at the 4-month landmark time point was associated with significantly longer OS [27]. The findings at this time point were also consistent with sensitivity analyses with alternative 2-and 6-month landmarks.…”
Section: Discussionsupporting
confidence: 59%
“…The landmark response analysis is an alternative approach to the standard partitioned survival model that allows for the modeling of long-term survival by response status [27,28]. A landmark response analysis was conducted for the nivolumab monotherapy data from CheckMate 032 [17].…”
Section: Landmark Response Analysismentioning
confidence: 99%